Simulation and fabrication of an integrated microfluidics chip for magnetic particle separation. - Hendrik Santoso Sugiarto. (2011)
In recent years, microfluidics devices hold many promises in a lot of biological applications. By combining electromagnetic structure and microfluidics channel, magnetofluidics chips can be fabricated, and the process involves photolithography technique to create a pattern for electromagnetic structure (microstripline) and microfluidics channel. The microfluidics chip utilizes two different kinds of physics, fluid dynamics and electromagnetism. One potential application of magnetofluidics chips is to employ magnetic force to isolate magnetic particles from nonmagnetic particles, which can be applied to separate two different cells. Later, this concept will be used for many bio-medical applications, especially for cancer treatment. In this report, several magnetic structures (i.e. magnetic bead, magnetic barcode, microstriplines) were modeled and their magnetic properties were analyzed. From the analysis of magnetic structure, the attraction force generated by the magnetic field can be investigated. This force was simulated to attract the magnetic moving bead under microfluidics channel to justify the concept of magnetofluidics chip from the theoretical side. The process of making magnetofluidics devices was also presented. The magnetofluidics devices then were used for demonstrating magnetic sorting and nonmagnetic-magnetic beads separation. This property can be used for many biological applications (i.e blood cleansing and cell separation).